Probiotic Properties of Lactobacillus plantarum RYPR1 from an Indigenous Fermented Beverage Raabadi - Yadav, Ruby; Puniya, Anil K.; Shukla, Pratyoosh (Frontiers in Microbiology, 2016)
Present study documents the potential probiotic Lactobacillus isolated from indigenous fermented beverage Raabadi, consumed during summers in Haryana and Rajasthan regions of India. A total of 5 Raabadi samples were collected aseptically and 54 isolates were purified using MRS medium. All the isolates were assessed for tolerance to low pH and bile salts. It was observed that out of 54 only 24 isolates could survive the simulated gastric conditions. These isolates were further evaluated in vitro for cell surface hydrophobicity, cell surface hydrophobicity, hypocholesteramic activity, anti-oxidative potential, BSH activity, antagonistic activity and antibiotic resistance profile. In addition, the confirmation of phenol resistance was also done. On the basis of results obtained, the survival rate of isolates was noted and 6 isolates were finally selected for further studies. Among them Lactobacillus plantarum RYPR1 and RYPC7 showed good survival at pH 2 which shows good acid tolerance. Moreover, Lactobacillus plantarum RYPR1 showed the highest hydrophobicity (79.13%) and represented the deconjugation of bile salts, which help in their adhesion to epithelial cells and colonization. Furthermore, RYPR1 also exhibited highest cholesterol reduction (59%) and subsequent analysis of results revealed that the above mentioned isolates further exhibit a good hypocholesterolemic effect and could be possibly used to prevent hypercholesterolemia. The present study divulges that Lactobacillus plantarum RYPR1 has an excellent probiotic potential.